Skin in the game: Epidermal molt as a driver of long‐distance migration in whales. Issue 2 (19th December 2019) - Pitman, Robert L.; Durban, John W.; Joyce, Trevor; Fearnbach, Holly; Panigada, Simone; Lauriano, Giancarlo
Abstract: Long‐distance migration in whales has historically been described as an annual, round‐trip movement between high‐latitude, summer feeding grounds, and low‐latitude, winter breeding areas, but there is no consensus about why whales travel to the tropics to breed. Between January 2009 and February 2016, we satellite‐tagged 62 antarctic killer whales ( Orcinus orca ) of four different ecotypes, of which at least three made short‐term (6–8 weeks), long‐distance (maximum 11, 000 km, round trip), essentially nonstop, migrations to warm waters (SST 20°C–24°C), and back. We previously suggested that antarctic killer whales could conserve body heat in subfreezing (to −1.9°C) waters by reducing blood flow to their skin, but that this might preclude normal (i.e., continuous) epidermal molt, and necessitate periodic trips to warm waters for routine skin maintenance ("skin molt migration, " SMM). In contrast to the century‐old "feeding/breeding" migration paradigm, but consistent with a "feeding/molting" hypothesis, the current study provides additional evidence that deferred skin molt could be the main driver of long‐distance migration for antarctic killer whales. Furthermore, we argue that for all whales that forage in polar latitudes and migrate to tropical waters, SMM might also allow them to exploit rich prey resources in a physiologically challenging environment and maintain healthy skin.